SCC-Ag, CYFRA 21-1 and chosen laboratory indices in monitoring treatment of patients with cancer of the uterine cervix - Jakubowicz, Jerzy; Rychlik, Urszula; Wójcik, Ewa; Brandys, Katarzyna; Tarapacz, Jadwiga (Contemporary Oncology/Współczesna Onkologia, 2006)
Objective: An attempt has been made to evaluate usefulness of SCC-Ag and CYFRA-21-1 determinations as well as the calculated on the basis of determinations of acidic alpha-1 glycoprotein and prealbumin, cancer serum index (CSI) in monitoring combination treatment (chemotherapy + brachytherapy + teleradiotherapy) and assessment of response to this treatment in cervical cancer patients. Material and methods: SCC-Ag, CYFRA-21-1, C-reactive protein, acidic alpha-1 glycoprotein and prealbumin concentrations were determined in the pilot group of 30 patients with cancer of the uterine cervix qualified to radio and chemotherapy followed with brachytherapy and in the reference group of 56 healthy controls. Results: In the studied group of cervical cancer patients, the diagnostic sensitivity values of the results of SCC-Ag and CYFRA 21-1 determinations, CSI, were: 77%, 63% and 67% respectively, at the assumed specificity of 95%. A significant relationship was observed between the concentrations of both markers. There was, however, no relationship found between the marker concentrations and the CSI values. After four treatment cycles, a significant decrease in concentrations of both markers, CRP as well as CSI values was observed. In the group of patients who responded well to treatment in comparison to those who responded badly (assessment made 3 months after the end of treatment) there were observed significantly lower pretreatment CRP and AAG levels with the lack of differences for the remaining indices. After four cycles of chemotherapy however, both the concentrations of CYFRA 21-1 and the CSI values were significantly lower in patients who responded well to treatment. In the group of patients with poor response to treatment, despite the falling tendencies observed, there were no significant differences in the levels of these indices, except for SCC-Ag. The analysis of ROC curves plots for SCC-Ag, CYFRA 21- 1 and CSI, as well as the differences in areas under these curves, did not show, however, any of the determined markers or CSI values to have high diagnostic sensitivity in differential diagnostics of patients responding well and those responding badly to treatment. Conclusions: In patients with cancer of the uterine cervix, the diagnostic sensitivity and specificity of the results of SCC-Ag and CYFRA 21-1 determinations and the CSI values are not much different. Lack of correlation between the marker concentrations and the CSI values justifies the use of this index as additional information in cervical cancer patients diagnostics. In cervical cancer patients, high pretreatment CRP level is associated with the increased probability of poor response to treatment.